backtracking monad
 Pietro Abate
[
Home
]
[ Index:
by date

by threads
]
[ Message by date: previous  next ] [ Message in thread: previous  next ] [ Thread: previous  next ]
[ Message by date: previous  next ] [ Message in thread: previous  next ] [ Thread: previous  next ]
Date:   (:) 
From:  Pietro Abate <Pietro.Abate@a...> 
Subject:  backtracking monad 
hi all, Can anyone help me to 'translate' this piece of haskell code [1] in ocaml ? I'm trying to learn how to program in monad style, but since I don't know haskell syntax (and almost all examples about monads are in haskell), I have some problems to understand what's going on here... I've got the general idea about monads, but the haskell syntax confuses me. Moreover I've also a general question about monads... I've the sensation that monads implementations are not tailrecursive. Is there a big overhead in using monads Vs Continuations (CPS) ? Where can I find a collections of basic monads (state, backtracking, continuation, etc) written in ocaml ? thanks, :) p  (* backtracking monad *) type MBt a = M [a] x `bindBt` f = x `bindM` \vs > foldr orelseBt failBt (map f vs) liftBt :: M a > MBt a liftBt m = m `bindM` \v > unitM [v] infixl 5 `apM` apM :: M (a > b) > M a > M b fm `apM` fx = fm `bindM` \f > fx `bindM` \x > unitM (f x) orelseBt :: MBt a > MBt a > MBt a x `orelseBt` y = unitM (++) `apM` x `apM` y failBt :: MBt a failBt = unitM []  this is my (failed) attempt ... (* state monad *) module M = struct type ('x, 'a) t = ('a > 'x) > 'x let bind m f x = m (fun a > f a x) let return x = fun s > x, s end (* backtracking monad *) module BtM = struct (* this list should be a lazy list *) type ('x ,'a) t = ('a, 'x list) M.t let return x = [x] let fail = return [] let orelse = ??? let bind m x f = List.fold_left orelse fail (List.map f x) end (* recursive mondad ?? *)  (* recursive mondad ?? *) type MRBt a = M (Ans a) data Ans a = Ans a (MRBt a)  NoAns x `bindRBt` f = x `bindM` \y > case y of NoAns > failRBt Ans v x' > f v `orelseRBt` (x' `bindRBt` f) liftRBt m = m `bindM` \v > unitM (Ans v failRBt) failRBt = unitM NoAns x `orelseRBt` y = x `bindM` \z > case z of NoAns > y Ans v x' > unitM (Ans v (x' `orelseRBt` y))  [1] http://www.math.chalmers.se/~augustss/AFP/monads.html  ++ Blog: http://blog.rsise.anu.edu.au/?q=pietro ++ ++ "All great truths begin as blasphemies." George Bernard Shaw ++ Please avoid sending me Word or PowerPoint attachments. See http://www.fsf.org/philosophy/nowordattachments.html